Phosphorıc Acıd Etchıng Vs. Sandblastıng Of Enamel For Dırect Bondıng Of Metallıc Orthodontıc Brackets - Zafer Sarı; Serdar Üşümez; Tancan Uysal (Galenos Yayinevi, 2001)
This study compared two methods of enamel conditioning; acid etching and sandblasting in terms of bond strengths yielded and type of failures occurred. Forty non-carious premolars extracted with orthodontic indication were used. The teeth were randomly divided into two groups of 20 each and were embedded in self cure acrylic in a vertical position so that the crowns were exposed. In the first group the teeth were etched with 37% phosphoric acid while 80 micron aluminum oxide particles were used in the other group. Stainless steel premolar brackets were bonded to all teeth with a standard procedure. Following thermocycling, the brackets were debonded with a chisel edge plunger in a universal test machine. Acid etching produced bond strength values of 8.2 ± 2.3 MPa which were statistically higher than that of produced by sandblasting; 6.8 ± 2.4 MPa. Our results indicate that sandblasting produced lower bond strength values with mainly adhesive type failure while all failure modes were observed in the acid etched sample. Sandblasting of enamel for enamel treatment is not advocated.